2023
DOI: 10.3389/fpubh.2023.1221142
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social isolation caused by the COVID-19 pandemic on the mood profile of active and sedentary older adults: physical activity as a protective factor

Alexandro Andrade,
Anderson D’Oliveira,
Keyla Mara dos Santos
et al.

Abstract: BackgroundThe COVID-19 pandemic has changed our habits and lifestyle due to social isolation and mobility restrictions. This new scenario, together with the fear of contracting the coronavirus, influenced mental health, especially among older adults, who presented reductions in social contact and physical activity (PA). Thus, the objective of the study was to analyze the impact caused by social isolation during the COVID-19 pandemic on the mood states of active and sedentary older adults.MethodsThis is an obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…We studied a specific population of older adult patients suffering from hip fracture, which is known to impact patient’s QOL. Indeed, the lack of exercise impacts QOL in the older adult ( 19 ), maybe more than COVID-19 did ( 5 ). The patients may have put the hip fracture impact on QOL more into perspective during the COVID period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied a specific population of older adult patients suffering from hip fracture, which is known to impact patient’s QOL. Indeed, the lack of exercise impacts QOL in the older adult ( 19 ), maybe more than COVID-19 did ( 5 ). The patients may have put the hip fracture impact on QOL more into perspective during the COVID period.…”
Section: Discussionmentioning
confidence: 99%
“…Then, many measures were taken, including mobility restrictions, curfews, restaurants and cultural areas closing, sanitary or vaccinal pass… It has already been reported that these measures may impact people’s quality of life, particularly older adult patients. Indeed, these patients are often already isolated and could suffer more from isolation due to all the measures taken to limit the pandemic ( 4 , 5 ). Many authors consider that older age is an obstacle for the “return to normal life,” as older patients are frail and helpless ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Social support and empathy are crucial in assisting individuals to cope with psychological stress during illness ( Mak et al, 2009 ; da Cruz et al, 2022 ). Conversely, Williams et al (2020) highlighted that those who maintained social distance and decreased social interaction during the pandemic reported negative impacts on mental health and wellbeing ( Andrade et al, 2023 ). Social support and empathy are crucial in assisting individuals to cope with psychological stress during illness ( Mak et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%